Pengembangan Media Pembelajaran EduGame Augmented Reality Bermuatan Pendidikan Karakter Pada Siswa Sekolah Dasar - Sahronih, Siti; Zakiyah Ismuwardani; Agil Suanto; Mia Rahma Shofari (LPPM POLITEKNIK LP3I BANDUNG, 2022)
The use of technology in the learning process is currently an attractive alternative choice to use. The dominance of the use of technology in the learning process is one of the things that must be achieved for many schools to provide fun learning services for students. The dominance of the use of technology must also be balanced with the output in the affective domain of students. Learning media to deliver messages in the learning process can include the value of character education such as through educational games. The use of Augmented Reality (AR) educational games containing the importance of character education can be used as an alternative choice. This research aims to create an application in the form of EduGame AR which is expected to foster the cultivation of character values in students as an alternative learning media. This study uses research and development methods using AR applications, then tested on elementary school student learning in the classroom. The results showed that the EduGame AR developed was very suitable for use in the student learning process with a practicality level of 88.76%.